Crystal chemistry, X-ray diffraction reference patterns, and bandgap studies for (BaxSr1–x)2CoWO6 (x = 0.1, 0.2, 0.3, 0.5, 0.7, and 0.9). Issue 3 (September 2020) - Wong-Ng, W.; Liu, G. Y.; Shi, D. D.; Yang, Y. Q.; Derbeshi, R.; Windover, D.; Kaduk, J. A.
Abstract : X-ray reference powder patterns and structures have been determined for a series of cobalt- and tungsten-containing cubic alkaline-earth perovskites, (Ba x Sr1– x )2 CoWO6 ( x = 0.1, 0.2, 0.3, 0.5, 0.7, and 0.9). The structure of the end members of the series, Sr2 CoWO6 and Ba2 CoWO6, were tetragonal and cubic, respectively, agreeing with the literature data. From Rietveld refinements, it was found that when x = 0.1 and 0.2, the structure was tetragonal I 4/ m ( a = 5.60481(6) and 5.62305(11) Å and c = 7.97989(12) and 7.9847(2) Å, respectively; Z = 2). When x > 0.2, the structure was cubic ( Fm $\bar{3}$ m, No. 225; Z = 4) (from x = 0.3 to 0.9, a increases from 7.98399(13) to 8.08871(10) Å). This tetragonal series of compounds exhibit the characteristics of a distorted double-perovskite structure. The bond valence sum values for the alkaline-earth (Ba, Sr) sites in all (Ba x Sr1− x )2 CoWO6 members are greater than the ideal value of 2.0, indicating over-bonding situation, whereas for the W sites, as x increases, a change from under-bonding to slightly over-bonding situation was observed. Density functional theory calculations revealed that while Sr2 CoWO6 is a semiconductor, Ba2 CoWO6 and SrBaCoWO6 are half-metals. Powder X-ray diffraction patterns of this series of compounds (Ba x Sr1− x )2 CoWO6, with x = 0.1, 0.2, 0.3, 0.5, 0.7, and 0.9, have been submitted to be included in the Powder Diffraction File.